Sentence production in Parkinson's disease. (2nd September 2018) - Dick, Jessica; Fredrick, Jennifer; Man, Grace; Huber, Jessica E.; Lee, Jiyeon
ABSTRACT: While growing evidence reports changes in language use in non-demented individuals with Parkinson's disease (PD), the presence and nature of the deficits remain largely unclear. Researchers have proposed that dysfunctioning fronto-basal ganglia circuit results in impaired grammatical processes, predicting qualitatively similar language impairments between individuals with PD and agrammatic Broca's aphasia, whereas others suggest that PD is not associated with language-specific grammatical impairment. In addition, there is a paucity of research examining syntactic production in PD at the sentence-level. This study examined sentence production of individuals with PD, healthy older adults, and individuals with agrammatic Broca's aphasia. In Experiment 1, using a Cinderella story-telling task, proportion of grammatical sentences, number of embedded clauses and production of verb arguments in sentences were examined. In Experiment 2, a structured sentence elicitation task was used in which syntactic complexity of sentences (canonical vs. non-canonical word order) was systematically manipulated while minimizing demands for non-syntactic processing. Only the participants with agrammatic Broca's aphasia showed significantly impaired syntactic production in both experiments. Participants with PD did not show impaired syntactic production in either task, despite impairments in lexical retrieval, repetition of words and sentences, and speech production. These findings suggest that impaired syntactic processing may not be a core deficit underlying the changes in language use in non-demented PD. Changes in language use in PD are qualitatively different from language deficits in aphasia.